Nothing to Hide: Aesthetic of Explicitness in the Transposition to Musical Theater of Spring Awakening - Vermal, Paz (Nota al margen, 2023)
In 2006, Broadway witnessed the premiere of the musical Spring Awakening, based on the late-nineteenth century German play with the same name, written by Frank Wedekind. In this analysis, we aim to study the transposition processes that can be observed between both of the pieces. We consider that, by means of expansive procedures and the exhibition of the theatrical statute, the musical piece resorts to an aesthetic of explicitness which intends to raise and develop, in a more outright way, the controversial themes already proposed by Wedekind.